Thermodynamic and environmental analysis of solar-driven supercritical water gasification of algae for ammonia synthesis and power production. (1st September 2021) - Liu, Shanke; Yang, Yan; Yu, Lijun; Li, Xuegang
Highlights: A novel system of solar-driven supercritical water gasification (SCWG) of microalgae for ammonia synthesis and power production was proposed. The system model was designed and the process simulations was implemented. Thermodynamic performance and environmental burdens were evaluated. The system has great advantages in terms of thermodynamics and environmental impact while it faces opportunities and challenges. Abstract: A novel system of solar-driven supercritical water gasification (SCWG) of microalgae for ammonia synthesis and power production was proposed to achieve chemical hydrogen storage with ammonia carrier. The system units mainly include SCWG, ammonia synthesis in supercritical water (SCW), power generation by supercritical water mixing fluid, organic Rankine circulating power generation, gas separation and circulating compression, and steam methane reforming. The system design and process simulation were implemented using Aspen plus. The thermodynamic performance of the system was analyzed. The life cycle environmental impact was evaluated with Simapro software. The results of thermodynamic analysis revealed that the energy efficiency, exergy efficiency, and energy consumption per ton of ammonia of the system were closely related to the microalgae concentration designed for the system. The simulation results presented the highest energy efficiency of 42.62% and exergy efficiency of 44.27% with the lowest energy consumption per ton of ammonia of 48.79 GJ/t. The circulating gas compressor was the largest electricity consumer and the heat loss of the coolers was the main reason for the energy loss of the system, indicating the direction of system optimization in the future. The evaluation of the life cycle environmental impact assessment showed that the plant operation stage contributed little to the overall environmental impact compared with the construction and dismantling stage. The values of the main midpoint indicator global warming potential (GWP) and endpoint indicator Human health could be as low as 0.69 kg CO2 -eq·kg −1 NH3 and 8.17 × 10 −5, respectively, under suitable design conditions. Compared with other ammonia synthesis routes, this work has great advantages in terms of thermodynamics and environmental impact, while it faces both opportunities and challenges. This research reveals the feasibility of SCWG of algae for ammonia synthesis and provides theoretical guidance for biomass cleaning conversion.